Algorithm for optimization of Viola-Jones object detection framework parameters - Egorov, A D (Journal of physics. Conference series, 2018)
The Viola-Jones algorithm is one of the most popular algorithms for objects recognition in an image. This research paper deals with the possibilities of parametric optimization of the Viola-Jones algorithm to achieve maximum efficiency of the algorithm in specific environmental conditions. It is shown that with the use of additional modifications it is possible to increase the speed of the algorithm in a particular image by 2-5 times with the loss of accuracy and completeness of work by not more than 3-5%.